ASAS KEWARGANEGARAAN GANDA ANAK DARI HASIL PERKAWINAN CAMPURAN - Wahyu, Diky; Qolba, Farikha Dawaa’a; Maharani, Chaesar Putri (Jurnal Res Justitia: Jurnal Ilmu Hukum, 2025)
With the enactment of Law No.12 of 2006 on the nationality of the Republic of Indonesia, which allows dual citizenship for children of mixed marriages, these children must comply with the jurisdictions of two different countries. The problem arising in international civil law is determining which country's law applies to their personal status. A possible solution for dual nationality children is that if they have habitual residence in Indonesia, which aligns with one of their nationalities, then Indonesian law will apply to their personal status. Conversely, if they have habitual residence abroad, they will be treated as foreign nationals.